Sound absorption performance of underwater anechoic coating in plane wave normal incidence condition. (April 2019) - Zhang, Z; Li, L; Huang, Y; Huang, Q
Abstract: On account of the theory of non-uniform waveguide and the wave propagation theory in layered media, a complete theoretical model is established for predicting the sound absorption performance of multi-layer underwater composite anechoic coating. Furthermore, the correctness of the theoretical calculation is verified by the finite-element simulation results. Then, the velocity nephograms corresponding the three absorption peak frequencies of the overburden are analyzed to reveal the sound-absorbing mechanism.